Antagonistic odor interactions in olfactory sensory neurons are widespread in freely breathing mice - Joseph D. Zak (Nature Portfolio, 2020)
Odor blends contain molecules that activate unique, overlapping populations of sensory neurons (OSNs). Here, by imaging OSN axon terminals, as well as their cell bodies within the olfactory epithelium, the authors find widespread antagonistic interactions in binary and complex odor mixtures.